Processing Agricultural Cornstalks toward High‐Efficient Stable Bifunctional ORR/OER Electrocatalysts. (2nd December 2021) - Li, Yinghui; Qu, Yuanju; Liu, Chaocheng; Cui, Jiedong; Xu, Ke; Li, Yang; Shen, Haoyu; Lu, Zhouguang; Pan, Hui; Xu, Tao; Liu, Detao
Abstract: Bifunctional oxygen reduction/oxidation reaction (ORR/OER) electrocatalysts derived from biomass are one of the most valuable materials in terms of sustainability, ecological economy and industrial manufacturing, and are emerging as a desired alternative to the commercial Pt/C and IrO2 catalysts. This work demonstrates the processing of agricultural cornstalk waste of cornstalks into stable bifunctional ORR/OER catalysts with high‐performance by a simple and cost‐effective strategy. Rich hydrophilic active groups (e.g., hydroxyl groups) in the hierarchical porous structures of the native cornstalks enable the sufficient facile combination with transition metals (e.g., Co, Fe, Zn) and heteroatoms (e.g., B, N) from soluble Co(NO3 )2, ZnCl2, H3 BO3, NH4 Cl in a hydrothermal reaction. The pyrolytic evaporation of Zn 2+ in a high‐temperature carbonization process facilitates the generation of abundant micropores and mesopores to increase specific surface areas (941.44 m 2 g −1 ) and also hinders aggregation between neighboring transition metals. The synergistic effects of N, B, Fe and Co doping in hierarchical porous biochar‐structures contributes to outstanding bifunctional ORR/OER activities and working stabilities, outperforming commercial Pt/C and IrO2 catalysts. Computational results further verify the valuable synergistic contributions based on density‐functional theory (DFT). This approach opens up a new possibility for the fabrication of bifunctional biochar‐based ORR/OER catalysts from artificial engineering and green processing for sustainable agricultural wastes. Abstract : Processing sustainable agricultural cornstalks toward difunctional oxygen reduction/oxidation reaction (ORR/OER) electrocatalysts with outstanding efficiency and stability, is shown to be promising alternative for the commercial Pt/C and IrO2 catalysts. This approach opens up a new view to design and fabricate renewable biochar‐based ORR/OER catalysts from artificial engineering and green processing of agricultural wastes.